Negative impact of anesthesia with midazolam, sufentanil, and propofol used in pediatric flexible bronchoscopy on the tracheal ciliary beat frequency in guinea pigs - Marta Joskova; Peter Durdik; Martina Sutovska; Marian Grendar; Dusan Koniar; Libor Hargas; Peter Banovcin; Sona Franova (Elsevier, 2020)
There is no direct evidence for the exact cilia-inhibitory effects of opioids, which are generally used to achieve general anesthesia in combination with other anesthetic drugs. These are the reasons, why we analysed direct concentration-dependent or systemic effects of anesthetics (propofol, sufentanil, and midazolam) at a recommended doses administered individually or simultaneously on the tracheal ciliary beat frequency (CBF) in in vitro experimental conditions. Brush biopsy technique was used to remove the tracheal epithelia of guinea pigs for microscopy evaluation of ciliary beating monitored by high-speed video camera and analysed by Ciliary Analysis software. The tracheal CBF was significantly lower in the presence of sufentanil (10−8 mol/L) than in the control group; similarly for midazolam-sufentanil (10−8 - 10−5 mol/L), as well as for midazolam-propofol (10−5 and 10−3 mol/L) combinations. The fact that concurrent administration of benzodiazepine significantly increased the risk of sufentanil-induced cilia-inhibition was pharmacologically confirmed using GABAA receptor antagonist, bicuculline methiodide. The benefit of propofol on the potent cilia-inhibitory effect achieved by benzodiazepine-opioid combination was non-significant. We highlight the pharmacodynamics interaction between anesthetic drugs mediated via GABAA receptor with negative impact on the CBF in a respiratory epithelium under experimental condition rather than the effect of individual anesthetic. Keywords: Total intravenous anesthesia, Anesthetic drugs, Pediatric flexible bronchoscopy, Ciliary beat frequency, Ciliary dyskinesia